2018
DOI: 10.1371/journal.pone.0199884
|View full text |Cite
|
Sign up to set email alerts
|

The increased purchase of asthma medication for individuals born preterm seems to wane with age: A register-based longitudinal national cohort study

Abstract: IntroductionPreterm birth is associated with increased risk of respiratory symptoms in childhood, often treated with asthma medication. We designed a follow-up study to previous research and investigated whether the association of gestational age with purchasing asthma medication diminishes in adulthood.MethodsWe conducted a register-based study of a national cohort of all infants born in Denmark in 1980–2009 evaluating longitudinal data on individually prescribed asthma medication (both inhaled ß-2 receptor a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 26 publications
3
9
0
Order By: Relevance
“…It did not find lower gestational age (GA) to be associated with higher rates of antibiotic prescription during the first year of life in children born with GA < 32 [11]. We previously found that treatment of asthma-like symptoms in childhood following preterm birth did not persist into adulthood [12,13], and hypothesized that similar a trend might be applicable for airway infections.…”
Section: Introductionmentioning
confidence: 99%
“…It did not find lower gestational age (GA) to be associated with higher rates of antibiotic prescription during the first year of life in children born with GA < 32 [11]. We previously found that treatment of asthma-like symptoms in childhood following preterm birth did not persist into adulthood [12,13], and hypothesized that similar a trend might be applicable for airway infections.…”
Section: Introductionmentioning
confidence: 99%
“…12,15,17 Damgaard et al 12 in a follow-up study showed a strong association between prematurity and purchase of prescribed asthma medications that weakened during adolescence. 14 The effect of gestational age was small beyond 11 years of age and gestational age per se did not seem to be significant for the development of asthma-like symptoms and most of its effect could be explained by other perinatal factors. Different results were reported by others.…”
Section: Resultsmentioning
confidence: 88%
“…The improvement in pulmonary function during childhood, and the decrease in association with birth weight or GA in some studies, 12,14 might in part be related to stricter definitions of atopic asthma and use of pulmonary function tests and allergy tests at school age, and less confounding effect of viral respiratory diseases that are common in preschool children. The impact of BPD and perinatal factors may decrease while genetic and environmental components might become more influential with time.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies suggest frequent use of asthma medications in childhood among former preterm infants, despite little data regarding their efficacy and safety (particularly for inhaled corticosteroids). 14 16 Among former preterm infants <29 weeks gestation with respiratory disease, patients from the Premature Respiratory Outcome Program cohort had increased exposure to bronchodilators and inhaled corticosteroids over the course of the first year of life, with a majority of patients receiving a prescription for at least one respiratory medication. 17 , 18 …”
Section: Introductionmentioning
confidence: 99%